The great urban transformation politics of land and property in China - Hsing, You-tien. (Oxford : Oxford University Press, 2010)
As China is transformed, relations between society, the state and the city have become central. 'The Great Urban Transformation' investigates what is happening in cities, and the development of quasi-property markets in China.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Urban policy -- China; Land use, Urban -- Economic aspects -- China; Land use, Urban -- Political aspects -- China; Urbanization -- China; Real estate investment -- China; China -- Social conditions -- 2000-; China -- Economic conditions -- 2000-; China -- Politics and government -- 2002-